KEKOSONGAN NORMA DALAM PENUNJUKAN PENJABAT DPRD PASCA PUTUSAN MK NOMOR 143/PUU-XXI/2023: TINJAUAN HUKUM TATA NEGARA - Ilhami, H. Yadi (SINERGI : Jurnal Riset Ilmiah, 2025)
Constitutional Court Decision No. 143/PUU-XXI/2023, which separated the implementation of national elections (2024) and regional elections (2026), has created legislative vacancies in the regions, particularly in the Regional People's Representative Council (DPRD), due to the lack of a legal mechanism governing the filling of DPRD positions during the transition period. This study aims to analyze the legal and governance implications of this vacancy and the urgency of establishing regulations as a normative solution. The research method used is normative juridical with a statutory and conceptual approach. The results indicate that the absence of a DPRD has the potential to create an imbalance between legislative and executive functions, reduce the principle of checks and balances, and threaten the legitimacy of local democracy. The absence of legislation to address this legislative vacancy also contradicts the principle of legal certainty. Therefore, immediate legislative action is needed to establish specific regulations to maintain the continuity of legislative institutional functions in the regions. This study recommends the establishment of transitional norms and further study of institutional design that adapts to changes in election schedules to ensure the stability of local democracy